Social Mind and Long-Lasting Disease: Focus on Affective and Cognitive Theory of Mind in Multiple Sclerosis - Isernia, Sara; Baglio, Francesca; d’Arma, Alessia; Groppo, Elisabetta; Marchetti, Antonella; Massaro, Davide (Frontiers in Psychology, 2019)
The role of social cognition, including Theory of Mind (ToM), in affecting quality of life (QoL) along the course of diseases has been reported. This is a considerable aspect in chronic pathologies, such as Multiple Sclerosis (MS), in which supporting and maintaining QoL is of crucial importance. We aimed to investigate the relation between ToM, clinical variables and neuropsychological profile in a cohort of adults with different clinical MS phenotypes (Relapsing Remitting -RR- versus Progressive -Pr). In particular, our study focuses on (1) how (affective and cognitive) ToM impairment occurs in different phenotypes, (2) whether MS ToM impairment is secondary to or independent from cognitive deficit and (3) whether ToM deficit impacts QoL. 42 adults with MS (18 M: 24 F, 52.38 ± 10.31 mean age, 26 RR and 16 Pr) and 26 matched healthy controls (HC) (7 M: 19 F, 51.35 ± 12.42 mean age) were screened with a neuropsychological and ToM battery, assessing both affective and cognitive components. We found statistically significant groups differences in cognitive but not affective ToM, with worse performance in PrMS compared to those with a RRMS disease course. Also, significant predictive effect of neuropsychological tests on ToM were identified in MS group. Finally, MS people with different level of affective ToM differed significantly in QoL. ToM deficit in moderately disabled people with MS involves cognitive but not affective ToM components with implications on QoL. It also appears to be related to cognitive performance. As neurological and neurocognitive profiles influence mentalizing in MS, ToM evaluation should be considered for inclusion in clinical screening.